2014
DOI: 10.15567/mljekarstvo.2014.0401
|View full text |Cite
|
Sign up to set email alerts
|

Production, composition and properties of mare’s milk

Abstract: U većini zemalja svijeta kobilje mlijeko oduvijek je bilo cijenjeno zbog svojih ljekovitih svojstava pa se danas sve više koristi u prehrambenoj, kozmetičkoj i farmaceutskoj industriji, te kao zamjena humanom mlijeku u prehrani novorođenčadi. Procjenjuje se da oko 30 milijuna ljudi u svijetu konzumira kobilje mlijeko. Posljednjih godina kobilje mlijeko postaje i u Hrvatskoj sve interesantniji proizvod zbog svog specifičnog sastava i svojstava. Kobilje mlijeko danas je predmet brojnih istraživanja i rasprava zb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…The selected method to identify plasma metabolites in our study was GC-MS, it is currently considered the gold standard for volatile organic compounds, the main limitations of this method are long analysis time and lack of possibility of real-time analysis or direct quantitative determinations. 33,34 The most frequent metabolites identified in the plasma of healthy foals were part of the carboxylic acid (amino acids), organooxygen (carbohydrates) and fatty acyls (fatty acids) classes. Most of these metabolites belonged to the amino acid and energy pathways which is expected as foals gain an average of 1-2 kg/day in the first few months of life.…”
Section: Discussionmentioning
confidence: 99%
“…The selected method to identify plasma metabolites in our study was GC-MS, it is currently considered the gold standard for volatile organic compounds, the main limitations of this method are long analysis time and lack of possibility of real-time analysis or direct quantitative determinations. 33,34 The most frequent metabolites identified in the plasma of healthy foals were part of the carboxylic acid (amino acids), organooxygen (carbohydrates) and fatty acyls (fatty acids) classes. Most of these metabolites belonged to the amino acid and energy pathways which is expected as foals gain an average of 1-2 kg/day in the first few months of life.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3 illustrates the butter production opportunities from camel milk however, the method of butter preparation from camel milk through the optimization of processing conditions are shown in Figure 4. The butter preparation from camel milk can be achieved by vigorous shaking of soured or fresh camel milk at higher temperature (24-25 0 C), and can recovered approximately 80% of the milk-fat (Brezovečki et al, 2015). Furthermore, preparation of clarified butter (Ghee) from camel milk revealed the lower yield and shelf life.…”
Section: Camel Milk Butter and Its Production Opportunitiesmentioning
confidence: 99%
“…Furthermore, preparation of clarified butter (Ghee) from camel milk revealed the lower yield and shelf life. The physical parameters indicated that camel milk butter are prominantly whiter in color and more viscous and soft or spreadable consistancy than butter obtain from other animal species (Brezovečki et al, 2015;Berhe et al, 2017). Additionally, camel rearing communities produce small amount of butter by using traditional methods and they usually utilized it for therpeutic and cooking purpose (Asresie et al, 2013).…”
Section: Camel Milk Butter and Its Production Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…An important aspect of improving foal VK status and reducing the risk of VKDB is the provision of VK to the neonate by milk. Most research investigating the composition and quality of mares' milk has been conducted in Western Europe (Krešimir et al 2011). Mare's milk has a composition different from that in most domestic species, but is relatively similar in composition to breast milk, and is frequently utilised as a substitute for infant's intolerant to cow's milk in some countries (Doreau and Boulot 1989;Pieszka et al 2016;Barreto et al 2019).…”
Section: Vk Status Of Foalsmentioning
confidence: 99%